Brit Mæhlum and Unn Røyneland: Det norske dialektlandskapet. - Kerswill, Paul (Norsk Lingvistisk Tidsskrift, 2016)
In setting about reviewing an undergraduate textbook on dialects in Norway, I am faced with some choices. I can evaluate its pedagogical value. Or else I can seize the opportunity to present the book for the benefit of a non-Norwegian reading audience, helping to make information about Norwegian dialects available to a wider readership. And finally, I can take the book as a piece of scholarly writing and evaluate it as such. Potential readers of this review will most likely want to know what the book tells us about language variation in what is often referred to as a ’sociolinguistic paradise’ (Røyneland 2009) - and this is the principal approach I will take.